The Failure of National Madrasah Science Competition Students in Solving Islam-Integrated Mathematics Problem on Triangle Material - Rofiki, Imam; Muhammad Zia Alghar (Universitas Negeri Surabaya, 2024)
Students, especially madrasah students, need to master Islamic integrated mathematics problem-solving. However, many madrasah students need help to solve Islamic-integrated mathematics problems. The failure occurs in one part and several interrelated parts of the solution. Therefore, this study aims to explore the failure of madrasah science competition students at the national level in solving Islamic integrated mathematics problems on triangle material. The research was conducted qualitatively on 29 students at the Madrasah Tsanawiyah (MTs) or equivalent level who participated in the national madrasah science competition, and they failed to solve Islamic integrated mathematics problems on triangle material. The research instrument was a triangle problem given during the National Madrasah Science Competition (KSM) in 2023. The results showed five categories of failure: failure to provide a correct and complete process, failure to integrate Islamic values, failure to use mathematical concepts, failure to use mathematical principles, and failure to apply relevant strategies. This research contributes to teachers by characterizing student failures that can be used as a guideline in designing learning strategies that can overcome student failures. In addition, teachers can provide scaffolding to students according to the type of failure.